Gabriel's Angel - Roberts, Nora (New York : Silhouette Books, 2023)
"All artist Gabriel Bradley wants is solitude to work on his painting and recover from the loss of his brother. But when a very pregnant--and very beautiful--woman ends up at his remote cabin during a blizzard, desperate, alone and on the run, the modern-day Scrooge cant bring himself to turn her away. Despite her intrusion, Laura brings Gabriel the gifts of passion, hope and life-- he just needs to find the courage to reach for them."--
Keywords: Pregnant women -- Fiction; Man-woman relationships -- Fiction; Single mothers -- Fiction; Male artists; Fiction; Blizzards -- Fiction; Colorado -- Fiction; Christmas fiction; Romance fiction